MOTIVASI INDONESIA MERATIFIKASI PERJANJIAN ASAP LINTAS BATAS “ASEAN AGREEMENT ON TRANSBOANDARY HAZE POLLUTION” TAHUN 2014 - Rahmi Deslianti Afni; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to explain the motivation of Indonesia to ratified the ASEAN Agreement on Transboandary Haze Pollution in 2014 AATHP was formed in 2002, which was signed by ASEAN countries and prevailed in 2003, which was initially ratified by six ASEAN countries, and up in 2010 has been ratified by nine countries. Indonesia is the last country to ratified this treaty in 2014, eventhough Indonesia is a country with the most frequent forest fires, and it happened almost every year.Forest fires in Indonesia has caused in air pollution that is not only detrimental to Indonesia, but also caused a pollution in other countries, especially in it self ASEAN region such as Malaisya and Singapore.This study uses the realism perspective where realism considers that a foreign policy will not be taken if it can not provide benefits to the country, so it become one of the reasons for Indonesia to ratified AATHP. This study also uses the theory of foreign policy with the level of the nation state analysis.The results of this study is, Indonesia ratified due AATHP in 2014 due to the Internal and external factors of Indonesia, which is one of the main purpose to be achieved after ratifying AATHP is Indonesia wants to take an important role in the policy making of the problems that occur on forest fires in Indonesia and also one of the internal factors which Indonesia ratified the problems of forest fires that can not be resolved until todayKeyword: AATHP, ASEAN, Forest Fires, Haze Pollution, Ratification, Agreement Cooperation